An overview of the Brazilian inselberg genus Ameroglossum (Linderniaceae, Lamiales), with the description of seven new species - Almeida, Erton M.; Christenhusz, Maarten J.M.; Wanderley, Artur Maia; Cordeiro, Joel Maciel P.; De Melo, José Iranildo Miranda; Da Costa Batista, Fabiane Rabelo; Felix, Leonardo P. (European Journal of Taxonomy, 2021)
Field studies of the inselberg flora of north-eastern Brazil have resulted in the discovery of much greater morphological diversity of the genus Ameroglossum, than previously envisaged. These enigmatic plants are endemic to isolated rock outcrops, which have long been surrounded by unsuitable habitat. The morphological forms are geographically isolated and stable in cultivation when grown under similar conditions. We here provide detailed descriptions of the two previously known species and propose an additional seven new species in the genus. A taxonomic revision of the genus, including an identification key is provided. We hypothesize that the evolution of this genus is driven by the diversity of their hummingbird pollinators. Due to the threatened nature of inselberg habitats and the small populations found for most taxa, the species described here are likely to be under threat and in need for formal redlisting.